HEDONIC PRICE OF FREE-RANGE EGGS IN COSTA RICA - Javier Paniagua; Johanna Solórzano; Barboza Navarro, David; Catalina Pérez (Applied Studies in Agribusiness and Commerce, 2023)
Eggs are a highly consumed animal product in Costa Rica. It is grown in different production systems and differentiation attributes, although there is little information about consumption and consumer preferences for grazing production. This study aimed to determine the effect of free-grazing on the price per kilogram of eggs paid by the consumer in Costa Rica. The results show a positive effect of 19.77% on price of eggs produced in free-grazing systems, but preference for other attributes such as nutritional fortification, egg size and brand names were also determined. Incorporating free-range technologies to replace caged poultry production can contribute to animal welfare and balance with nature, and producers can opt for differentiated prices in local markets.